THREE DIMENSIONAL MODELING OF SEDIMENT TRANSPORT IN ESTUARY OF MAHAKAM DELTA : ABSTRACT - Tarya , Ayi
Abstract: In this study, a three-dimensional baroclinic hydrodynamics and sediment transport model ECOMSED developed by HydroWual, Inc., (2002) has been applied in Estuary of Mahakam Delta, East Kalimantan, to study the dynamics of current and sediment transport in the region. The model was run for 1 year simulation (January December 2005) using river discharges and tides as generating forces. The simulation results of the hydrodynamics model show that at flood condition and highest water, the waters flow into the delta, while at ebb condition and lowest water, it flows toward the sea (Makassar Strait). At Muara Pegah, Muara Jawa, Muara Kaeli and Muara Pantauan, the magnitude of currents during the one year period of simulation ranges about 0.40 0.60 m/s, stronger than those at Muara Pemankaran, Muara Berau and Muara Badak which ranges about 0.10 0.20 m/s. The different of current speed between surface and bottom layer at Muara Jawa is about 0.15 m/s and at Muara Pegah is about 0.80 m/s. The simulation results of the sediment transport model show that sediment concentration and current speed are correlated to each other. The correlations are in the sense that high concentration of sediment is associated with stronger currents. At Muara Jawa, Muara Pegah, Muara Pantauan and Muara Kaeli, sediment concentration at surface layer is mainly influenced by seasonal variation of river discharges. Range of sediment concentration is about 160 306 mg/l. whereas at Tanjung Bayur it is dominantly influenced by tides, range of sediment concentrations is about 250 320 mg/l. Sediments from Mahakam River are mainly transported toward Muara Jawa and Muara Pegah rather than to Muara Berau and Muara Bayur. The different of sediment concentration between surface and bottom layer at Muara Pegah is about 0.5 4 mg/l at wet season, whereas at dry season is about 3 10 mg/l. Maximum front distance from Muara Pegah in February is about 18.6 km and minimum in October (about 13.2 km). Time lag between sediment concentration and elevation is about 6 hour.